Knowledge and attitudes towards dementia among final-year medical students in Brazil - Jacinto,Alessandro Ferrari (2017)
Summary Objective: Among all countries, Brazil is expected to have the sixth largest elderly population in 2025. Dementia syndromes are prominent among aging-related diseases. Despite the necessity of and curriculum for training in geriatric medicine to make recommendations on an approach to this theme, adequate training appears to be infrequent. The present study aimed to evaluate the knowledge about dementia and students' attitude towards it during the last semester of the medical course in two of the most important Brazilian medical schools. Method: In our study, a sample of 189 students was invited to complete questionnaires comprising demographic and professional topics, knowledge with respect to cognitive alterations in the elderly and attitudes in dealing with an elderly patient with dementia. Results: A total of 155 students accepted to participate in the study; 92(59.7%) considered that they had good training in cognitive alterations during their undergraduate medical course, while 67 (58.8%) of them declared having had only theoretical training. Regarding knowledge, the students obtained a mean of 6.9, out of a scale from 0 to 14 points. As for attitudes, the students agreed that they can contribute to the life quality of the patient and of the caregiver, and that it is useful to provide the diagnosis to the family. Conclusion: The findings of this study are relevant for overturn the educational barriers of physicians in relation to the care of patients with dementia.